Mothers’ Legal Awareness of Labeling and Health Information on Household Supplies in Baby Diapers - Renita Andriyani; Eny Sulistyowati; Rosa Oktavia Iskandar (Universitas Negeri Surabaya, 2025)
The Ministry of Health through Regulation Number 62 of 2017 has mandated that baby diaper products, as part of Household Health Supplies (PKRT), must include proper markings and product information before distribution. This regulation ensures consumer safety and compliance with health standards. This study aims to analyze the level of legal awareness among mothers regarding PKRT markings and information on baby diaper products, and identify the factors influencing that awareness. Conducted in Pasongsongan Sub-district, Sumenep Regency, East Java, the study applies an empirical juridical research method using interviews, observation, and documentation as data collection techniques. The findings reveal that mothers’ legal awareness is generally low, as assessed through four key indicators: legal knowledge, legal understanding, legal attitudes, and legal behavior. Most mothers lack awareness of the obligation for producers to include PKRT markings, and this is reflected in their indifferent behavior when selecting baby diapers. Contributing factors to this low awareness include limited reading interest, low levels of education, and age-related constraints. The study concludes that the legal awareness of mothers as consumers remains insufficient and recommends that relevant authorities, including health offices and consumer protection agencies, intensify socialization and education regarding the importance of PKRT markings and information. Increasing public literacy and access to clear, comprehensible labeling on household health products is essential to enhance consumer protection and public health standards.